A new species of Cryptocellus (Arachnida, Ricinulei) from Oriental Amazonia - Pinto-Da-Rocha, Ricardo; Bonaldo, Alexandre B. (Zootaxa, 2007)
Cryptocellus tarsilae n. sp. is described from male and female specimens collected in a small cave at Carajás National Forest, Serra Norte, Pará, Brazil. The new species appears to be similar to C. peckorum Platnick & Shadab, 1977 by the moderately expanded metatarsus III, bearing a metatarsal process with a flattened tip. Both males and females of the new species are readily recognizable by the carapace having a posterior median bulge covered by tubercles.